Elastosonography and electrodiagnosis in relation to symptomatic and functional grading of carpal tunnel syndrome - Marwa Yahia,; Ahmed El Shambaky,; Doaa Lasheen, (Archives of Rheumatology, 2023)
Objectives: This study focused on the symptomatic and the functional evaluation in correlations to median nerve elasticity, its ultrasound parameters, and the electrodiagnostic grading of primary carpal tunnel syndrome (CTS) patients. Patients and methods: In the case-control study, 100 wrists of 57 CTS patients (54 females, 3 males; mean age: 39±9.8 years; range, 20 to 60 years) clinically diagnosed according to the American Academy of Neurology Clinical Diagnostic Criteria were evaluated between December 2019 and December 2020. The control group included 110 nondiseased wrists of 55 sex- and age-matched healthy subjects (males 7, females 48; mean age: 35.7±10.3 years; range 20 to 58 years). Functional assessment using Hi-Ob-Db clinical scale, electrodiagnosis, ultrasonographic screening, and elasticity evaluation were done for all patients. Results: CTS patients had an increased stiffness of the median nerve compared to controls. Functional stages were positively correlated with the ultrasonographic parameters and the electrodiagnostic stages of CTS. The elastogram of clinically diagnosed patients was revealed more stiffness of the MN, with negative electrodiagnosis results. Conclusion: Clinically diagnosed CTS could be missed by the electrodiagnosis but then properly figured by ultrasonography and potentially graded by sonoelastography. Sonoelastography may be an effective method for early diagnosis and appropriate grading of CTS.